Beyond Financial Reporting: A Journey from Sustainability towards Integrated Reporting - Mio, Chiara; Fasan, Marco (Journal of Environmental Accounting and Management, 2026)
The present study provides an overview of the evolution of non-financial disclosure over time, from sustainability towards integrated reports. The article tackles three different themes. First, it introduces the concept of NFI, and it discusses why such information is relevant in the current business environment. It revises previous literature in order to answer to the question “why do companies invest inCorporate Social Disclosure (CSD)”? Second, it defines and discusses the topic of Integrated Reporting (IR). Third, it provides an analysis ofthe state of the art of CSD and IR nowadays. The study shows that policy makers are increasingly pushing companies towards NFI disclosure and that, at the same time, companies have incentives in engaging in NFI disclosure, as shown by previous academic literature. While sustainability reporting is a well-established reality, IR still needs to be further developed, and this study proposes some avenues for future research.